A intergeracionalidade quilombola: o caso da comunidade Adelaide Maria Trindade Batista em Palmas - PR - Silva, Maria Isabel Cabral da (2021)
The dissertation The quilombola intergeracionality: the case of Adelaide Maria Trindade Batista in Palmas - PR presents the narrative of the quilombolas women, pervaded by the cultural historicity of the comunnity reffered. For this purpose, we defined as a general obejective: the cultural markers that are used to define the quilombola women identity among the different genarations. We selected the following specific objectives: to identify how the societal bond is produced among the community women in different generations; to comprehend the relations between different forms of knowledge for the testimony women; to know the speech about being a quilombola into circulation in the community. The research issue was the questioning: How the women intergeracionality relations are established among them in the Adelaide Maria Trindade Batista Comunnity? From this inquiry the research issues were demarcated: How the societal bonds are produced among women in the community? Which are the knowledge forms that circulate in the community and that subjectivate the interviewed women? Which are the speeches about the quilombola person that is the greatest power of subjectivation between the testimonies group? The theoretical and methodological foundation that orientated the research were the contributiions of authors like Ramos (2015), Mattos (2004), Silva (2018), Geertz (1989), Bauer (2002), Santos (2005), among others, that helped to understand the studied phenomenon. It is a qualitative work, which we used the methodological procedure of the Cultural Studies in the ethnographic modality in order to respond the investigation purposes. The writting denoument occured from narrative interviews with five quilombola women, with the purpose of analizing the relations among the different knowledge forms, the social bonds estabelished by those women and the speech about being a quilombola into circulation in Adelaide Maria Trindade Batista quilombola community. The interviews showed how much these women seek out for visibility and respect, taking all the responsability of the community cultural memory maintenance.